2012
DOI: 10.1177/1071181312561017
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evaluation of the Emotiv EPOC BCI Headset for the Detection of Mental Actions

Abstract: This study evaluated the detection accuracy of one of the first brain-computer interfaces intended for personal use by normal, healthy users: the Emotiv EPOC. This system allows the user to directly interact with computer software through thoughts alone. The system was evaluated on its ability to accurately detect and classify six sets of paired mental actions over three evaluation phases. Results found the system to perform significantly better than chance for all mental actions, and improve over time with ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 7 publications
0
10
0
3
Order By: Relevance
“…1). A pesar de ser dispositivos de relativo bajo costo, los dispositivos Emotiv registran la actividad cerebral para la detección de diversas acciones mentales con éxito [3], [4]. El dispositivo Emotiv provee, además de las señales cerebrales medidas directamente de los sensores, seis medidas básicas de desempeño mental estimadas directamente a partir de la actividad cerebral: Compromiso (Engagement), Interés (Interest), Excitación (Excitement), Enfoque (Focus), Estrés (Stress) y Relajación (Relaxation).…”
Section: Antecedentesunclassified
“…1). A pesar de ser dispositivos de relativo bajo costo, los dispositivos Emotiv registran la actividad cerebral para la detección de diversas acciones mentales con éxito [3], [4]. El dispositivo Emotiv provee, además de las señales cerebrales medidas directamente de los sensores, seis medidas básicas de desempeño mental estimadas directamente a partir de la actividad cerebral: Compromiso (Engagement), Interés (Interest), Excitación (Excitement), Enfoque (Focus), Estrés (Stress) y Relajación (Relaxation).…”
Section: Antecedentesunclassified
“…The Emotiv system is a low-density electrode EEG device that collects a veracious signal of underlying cortical activity, and has been used in prior studies published in leading business journals (Minas, Potter, Dennis, Bartelt, & Bae, 2014). Many studies have scrutinized the Emotiv device in a variety of settings such as examining working memory (Wang, Gwizdka, & Chaovalitwongse, 2016), auditory event-related potentials (ERPs) (Badcock et al, 2013), mobile brain-computer interfaces (Debener, Minow, Emkes, Gandras, & Vos, 2012), reliable detection of the P-300 wave and other ERPs (Ramírez-Cortes, Alarcon-Aquino, Rosas-Cholula, Gomez-Gil, & Escamilla-Ambrosio, 2010;Wang et al, 2016), human-computer interaction research (Taylor & Schmidt, 2012), hemispheric asymmetry (Friedman, Shapira, Jacobson, & Gruberger, 2015), among others. These studies have found Emotiv obtains a reliable and valid signal of underlying cortical activity and has been shown to be as good as larger high-density systems.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…Textile ECG electrodes are placed on the thorax, and textile piezoresistive sensor (breathing sensor) is placed above them in the middle (9). Emotiv EPOC® neuroheadset is a wearable 14-channel EEG system, validated as brain computer interface (BCI) device (10,11), used in the research of event-related potential (ERP) studies (12,13) and emotion recognition experiments (14,15). Myo armband® is a hand gesture controller that integrates eight segments with electromyography (EMG) sensors (each segment includes one EMG amplifier with bar electrodes), and one segment additionally includes a three-axis accelerometer and a three-axis gyroscope (16).…”
Section: Introductionmentioning
confidence: 99%